Anti-Mayaro virus activity of a hydroethanolic extract from Fridericia chica (Bonpl.) L. G. Lohmann leaves - Lopes, Gabriela F.M.; Lima, Willam G.; Santos, Felipe R.S.; Nunes, Damiana A.F.; Passos, Maria J.F.; Fernandes, Simone O.A.; de Magalhães, José C.; dos Santos, Luciana L.; Ferreira, Jaqueline M.S. (Journal of ethnopharmacology, 2022)
Mayaro fever is a neglected tropical disease. The region of the most significant circulation of the Mayaro virus (MAYV) is the Amazon rainforest, situated in remote areas that are difficult to access and where medicine is scarce. Thus, the regional population uses plants as an alternative for the treatment of various diseases. Fridericia chica is an endemic plant of tropical regions used in traditional medicine to treat fever, malaise, inflammation, and infectious diseases such as hepatitis B. However, its antiviral activity is poorly understood.ETHNOPHARMACOLOGICAL RELEVANCEMayaro fever is a neglected tropical disease. The region of the most significant circulation of the Mayaro virus (MAYV) is the Amazon rainforest, situated in remote areas that are difficult to access and where medicine is scarce. Thus, the regional population uses plants as an alternative for the treatment of various diseases. Fridericia chica is an endemic plant of tropical regions used in traditional medicine to treat fever, malaise, inflammation, and infectious diseases such as hepatitis B. However, its antiviral activity is poorly understood.This study aimed to investigate the anti-MAYV activity of the hydroethanolic extract of the leaves of Fridericia chica (HEFc) in mammalian cells and its possible mechanism of action.AIM OF THE STUDYThis study aimed to investigate the anti-MAYV activity of the hydroethanolic extract of the leaves of Fridericia chica (HEFc) in mammalian cells and its possible mechanism of action.The antiviral activity of HEFc was studied using Vero cell lines against MAYV. The cytotoxicity and antiviral activity of the extract were evaluated by the 3-(4, 5- dimethyl-2-thiazolyl)-2, 5-diphenyl-2H-tetrazolium bromide (MTT) assay. The overall antiviral activity was confirmed by the plaque forming units (PFU) method. Then, the effects of HEFc on MAYV multiplication kinetics, virus adsorption, penetration, and post-penetration, and its virucidal activity were determined in Vero cells using standard experimental procedures.MATERIALS AND METHODSThe antiviral activity of HEFc was studied using Vero cell lines against MAYV. The cytotoxicity and antiviral activity of the extract were evaluated by the 3-(4, 5- dimethyl-2-thiazolyl)-2, 5-diphenyl-2H-tetrazolium bromide (MTT) assay. The overall antiviral activity was confirmed by the plaque forming units (PFU) method. Then, the effects of HEFc on MAYV multiplication kinetics, virus adsorption, penetration, and post-penetration, and its virucidal activity were determined in Vero cells using standard experimental procedures.HEFc exerted a effect against viral infection in Vero cells at a non-cytotoxic concentration, and no virion was detected in the supernatant in a dose-dependent and selective manner. HEFc inhibited MAYV in the early and late stages of the viral multiplication cycle. The extract showed significant virucidal activity at low concentrations and did not affect adsorption or viral internalization stages. In addition, HEFc reduced virions at all post-infection times investigated.RESULTSHEFc exerted a effect against viral infection in Vero cells at a non-cytotoxic concentration, and no virion was detected in the supernatant in a dose-dependent and selective manner. HEFc inhibited MAYV in the early and late stages of the viral multiplication cycle. The extract showed significant virucidal activity at low concentrations and did not affect adsorption or viral internalization stages. In addition, HEFc reduced virions at all post-infection times investigated.HEFc has good antiviral activity against MAYV, acting directly on the viral particles. This plant extract possesses an excellent and promising potential for developing effective herbal antiviral drugs.CONCLUSIONSHEFc has good antiviral activity against MAYV, acting directly on the viral particles. This plant extract possesses an excellent and promising potential for developing effective herbal antiviral drugs.